Integrin Inhibitor Suppresses Bevacizumab-Induced Glioma Invasion()() - Ishida, Joji (Neoplasia Press, 2014)
Glioblastoma is known to secrete high levels of vascular endothelial growth factor (VEGF), and clinical studies with bevacizumab, a monoclonal antibody to VEGF, have demonstrated convincing therapeutic benefits in glioblastoma patients. However, its induction of invasive proliferation has also been reported. We examined the effects of treatment with cilengitide, an integrin inhibitor, on bevacizumab-induced invasive changes in glioma. U87ΔEGFR cells were stereotactically injected into the brain of nude mice or rats. Five days after tumor implantation, cilengitide and bevacizumab were administered intraperitoneally three times a week. At 18 days after tumor implantation, the brains were removed and observed histopathologically. Next, the bevacizumab and cilengitide combination group was compared to the bevacizumab monotherapy group using microarray analysis. Bevacizumab treatment led to increased cell invasion in spite of decreased angiogenesis. When the rats were treated with a combination of bevacizumab and cilengitide, the depth of tumor invasion was significantly less than with only bevacizumab. Pathway analysis demonstrated the inhibition of invasion-associated genes such as the integrin-mediated cell adhesion pathway in the combination group. This study showed that the combination of bevacizumab with cilengitide exerted its anti-invasive effect. The elucidation of this mechanism might contribute to the treatment of bevacizumab-refractory glioma.